Different Attributing Factors of Anemia among Pregnant Women - Parveen, Naheed; Shaikh, Farhana; Siddiqui, Erum; Abbasi, Madiha (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To determine the different attributing factors which are contributing to increase the frequency of anemia in pregnancy. METHODOLOGY: This descriptive observational study conducted at Obstetrics and Gynecology unit II, Liaquat University of Medical & Health Sciences Jamshoro, from July to December 2017. Consent was taken. Samples were collected from all the pregnant women with anemia presented in second and third trimester; their recent reports of Hemoglobin percentages were checked. Women with singleton pregnancies whether primigravida or multigravida and before delivery were included, patients with medical problems leading to anemia like renal, cardiac, lung diseases and hemoglobinopathies were excluded. The variables were age, parity, education, antenatal status nutritional factors such as habit of chewing chalia (betal nuts), pan, pica of mud (multani miti), vegetarian or non vegetarian, consumption of type of meat red, white meat and inquired about worm infestation. RESULTS: A total 131 pregnant women, 57 (43.5%) were between 26 to 33 years of age group, 58 (44.3%) uneducated, 70 (53.4%) were antenatally booked. Most of 54 (41.2%) were between 36- 41 weeks of gestation and 79 (60.3%) were multigravidas. The non-vegetarian 122 (93.1%) were taking meat, in which 67 (51.1%) were taking chicken. In 72 (60.5%) of women had habit of chewing chalia, pica of mud in 16 (12.2%) and worm infestation seen in 10 (7.6%) of pregnant women. CONCLUSION: The pregnant women should be counseled for the risk of anemia with their dietary habits of non-nutritious substances, because these factors ultimately leads to iron deficiency anemia in pregnancy.